Solution for Complex Amplitude in LCD Removal Algorithm - Chomitz, Hanna Gjermo; Lievsay, James R.; Jackson, Julie Ann (Proceedings of the IEEE National Radar Conference (1996), 2021)
Large clutter discretes (LCDs) are spectrally bright localized clutter that can cause false alarms or missed target detections in space-time adaptive processing (STAP) data. For passive bistatic STAP, the LCD removal (LCDR) algorithm estimates the spatial/Doppler frequency and complex amplitude of the LCD and then removes it from the data. However, previous techniques to estimate the LCD's amplitude were complicated and slow. This paper proposes a method that directly solves for the amplitude that minimizes the power output at the LCD's spatial/Doppler frequency.